Digital health technologies and self-efficacy in Parkinson’s: a scoping review - Victoria Allgar; Edward Meinert; Camille B Carroll; Andrew Michael Hall (BMJ Open)
Objective Prior research has identified that people with Parkinson’s reporting lower levels of self-efficacy exhibit worsening motor and non-motor symptomology, reduced quality of life, and self-management. Our key objective was to conduct a scoping review examining the impact of digital health technologies on self-efficacy in people with Parkinson’s.Design A scoping review using Arksey and O’Malley’s (2005) framework was undertaken.Data sources MEDLINE, Embase, PsychINFO, CINAHL, Web of Science, IEEE Xplore, and Google Scholar principally for grey literature were searched from 1 January 2008 to the 24th of July 2024.Eligibility criteria for selecting studies Primary studies which incorporated digital health technologies, measured self-efficacy and had a sample population of people with Parkinson’s were searched.Data extraction and synthesis Following identification of potentially eligible records, two independent reviewers undertook title and abstract screening, followed by full-text screening. Data was extracted using our earlier published data extraction sheet which incorporated the Practical Reviews in Self-Management Support (PRISMS) taxonomy, and the template for intervention description and replication (TIDieR) checklist. Data was extracted from a Microsoft Excel spreadsheet and synthesised by describing themes, demographic data and numerical data.Results From 33 165 unique records following screening and independent review by two reviewers, 11 eligible records were found. Of these five elevated self-efficacy to a statistically significant level, five did not and one lowered self-efficacy. Of the studies which raised self-efficacy to a statistically significant level, all adopted a multimodal approach with a variety of devices. Thematically, these devices were focused on physical activity, falls/falls prevention, or both. The level of heterogeneity precluded comparisons between studies.Conclusions This scoping review identified significant knowledge and evidence gaps in the literature, and the limited number of eligible studies make these findings not generalisable. Future self-management research might benefit from also considering self-efficacy.